BRIDGING ART AND COMMUNITY : AN ENTRY POINT TO FORMATION OF ART KNOWLEDGE DEVELOPMENT - Mohamad Faizuan, Mat; Mohamad Zamhari, Abolhasan; Sylvester Wielding, Jussem; Hishamuddin, Siri (IJIDECS, 2018)
Visual art scene and their surrounding communities have failed to work cooperatively to address art knowledge development issues. Fortunately, some visual artists and public universities have begun to change and support towards art knowledge development and their communities. We believe that art can bridge people together and develop art knowledge among the community. We also believe in active participation and by giving it back to them. However, what are the mechanisms to bring art to the society and what is the benefit that we can offer to the society? This paper highlights the roles of art in benefiting towards our community. Samples of our curatorial works that emphasized community and art knowledge development in previous project will be discussed.